PENGARUH IKLIM ORGANISASI SEKOLAH, SELF EFFICACY, GAYA KEPEMIMPINAN DAN KOMITMEN PROFESIONAL TERHADAP KINERJA DENGAN KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL SEBAGAI MEDIASI (Studi Pada Guru SMA Negeri se Kabupaten Batang Rayon Timur) - 11.52.02.0130, Lilik Retno Willianti (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study was to analyze the "Effect of School Organizational Climate, Self Efficacy, Leadership Style and Professional Performance Against Commitment to Job Satisfaction and Organizational Commitment as Mediating. The method used is descriptive quantitative, seeking independent variables affect the dependent variable. Primary data obtained from the survey questionnaire as a data collection tool, the secondary data obtained through oral information from the school that became the object of research. Regression test results indicate that the independent variables, namely self-efficacy has a direct influence on performance. Leadership style has a direct influence on performance. Organizational commitment mediates professional commitment to the performance of job satisfaction mediates professional commitment to performance. Organizational commitment mediates the school organizational climate on performance. Job satisfaction and organizational commitment mediates professional commitment to performance. Key Words:Organizational Climate Education, Self Efficacy, Leadership Style, Professional Commitment, Job Satisfaction, Organizational Commitment and Performance